(untitled) (Journal of Hama University, 2019)
Referring to the importance of government procedures and their impact on various sectors, all governments - in the last two decades - have adopted the concept of e-government, which means integration of various stand-alone governmental systems into interoperability framework to exchange data securly and provide e-services for the governmental participants (G2G), for business sector (G2B) or for citizens (G2C). Several methodologies have been developed to implement e-government projects such as (e-Gif, EA, CORBA and SOA).In the last few years, service-oriented architecture (SOA) has proven its efficiency in integrating distributed applications. In this paper, we will review the methodology of service-oriented architecture (SOA) and the related works that adopted this methodology, asa preface to the proposed solution to activate the Syrian e-government initiative, which faces a range of challenges hindering its effective implementation